2017
DOI: 10.17977/um001v2i42017p142
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Tingkat Perilaku Agresi Berdasarkan Jenis Kelamin pada Siswa Sekolah Menengah Kejuruan Kota Yogyakarta

Abstract: Abstract:The purpose of this study is to identify whether there are differences between male student aggression behavior and female students aggresive behavior in Yogyakarta. This comparative study involved 160 students from Sekolah Menengah Kejuruan Muhammadiyah in Yogyakarta as a sample. Simple Random Sampling technique were used to choose sample. The instrument used is the scale of aggression behavior. Independent Samples Test were used to analysis the data. The research findings show that there is no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
1
10
0
7
Order By: Relevance
“…Other studies on junior high schools in Yogyakarta showed the data on aggressive behavior of 1% of students were categorized as very aggressive; 13% of students were aggressive; 37% of students were quite aggressive; 43% of students were fairly aggressive; and 6% of students were somewhat aggressive (Alhadi, Purwadi, Muyana, Saputra, & Supriyanto, 2018). In fact, in Yogyakarta, the level of aggressive behavior in female students tends to be equal as in male students (Saputra, Hanifah, & Widagdo, 2017). This draws attention from many parties about this complicated problem of aggressiveness in Indonesia.…”
Section: Introductionmentioning
confidence: 93%
“…Other studies on junior high schools in Yogyakarta showed the data on aggressive behavior of 1% of students were categorized as very aggressive; 13% of students were aggressive; 37% of students were quite aggressive; 43% of students were fairly aggressive; and 6% of students were somewhat aggressive (Alhadi, Purwadi, Muyana, Saputra, & Supriyanto, 2018). In fact, in Yogyakarta, the level of aggressive behavior in female students tends to be equal as in male students (Saputra, Hanifah, & Widagdo, 2017). This draws attention from many parties about this complicated problem of aggressiveness in Indonesia.…”
Section: Introductionmentioning
confidence: 93%
“…Subjects in the research conducted at the junior high school level specifically had different levels of development from vocational students but still had similarities, namely the subjects were in the adolescent phase. When viewed from gender, there was no difference in the level of aggressiveness between female students and male students (Saputra, Hanifah, & Widagdo, 2017).…”
Section: Introductionmentioning
confidence: 80%
“…Sedangkan pada variabel agresivitas menyebutkan bahwa setiap individu baik perempuan maupun laki-laki kemungkinan besar akan terlibat dalam perilaku agresif. Namun, keterlibatan laki-laki dalam perilaku agresif lebih cenderung pada agresi relasional teman sebaya baik proaktif maupun reaktif terhadap situasi tertentu sedangkan keterlibatan perempuan dalam perilaku agresif cenderung melakukan agresi relasional romantis (Saputra, Hanifah & Widagdo, 2017).…”
Section: Pembahasan Dan Kesimpulanunclassified